Out of Sarawak, Further Records Red-blue big-jawed spider Leucauge sarawakensis (Arachnida: Araneae) in Southeast Asia - RACHMAN, NUR; ALI, MUHAMMAD SAYIDINA; EFFENDI, SURIANTO; IQBAL, MUHAMMAD (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Red-blue big-jawed spider Leucauge sarawakensis is a spider species described in 2015 from specimens collected in Sarawak, Malaysian Borneo. Since 2015, there are many records of L. sarawakensis reported by citizen science platform. To update recent distribution of L. sarawakensis, we compile distribution of the species from confirmed reports and our observations. This study suggest L. sarawakensis recorded far away out c. 1.000 km distance from Sarawak, and distribution of this species range from Vietnam, Thailand, Malaysia, Singapore, Brunei and Indonesia (Sumatra and Kalimantan)